Thermal Contact Conductance - Madhusudana, Chakravarti V. (Mechanical Engineering Series,, 2014)
This book covers both theoretical and practical aspects of thermal contact conductance. The theoretical discussion focuses on heat transfer through spots, joints, and surfaces, as well as the role of interstitial materials (both planned and inadvertent). The practical discussion includes formulae and data that can be used in designing heat-transfer equipment for a variety of joints, including special geometries and configurations. The material included in this edition has been updated to reflect the latest advances in the field.